Budget Constraints and Expanding of Non-Governmental Organizations Participation in the Implementation of State's Social Policies - TATUEV, Arsen A.; KEREFOV, Murat A.; OVCHAROVA, Nataliya I.; VILISOVA, Maria L.; SHIBZUHOVA, Renata A. (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
Nowadays, the implementation of state's social policies becomes critically urgent in the context of social development for all countries of the world. For a number of objective reasons, the state is forced to reduce its obligations to a certain extent in the social sphere in such a way as to avoid hampering the markets development. The objective of the current study is to identify the priorities of modern public administration. The structure of budget expenditures demonstrates shifting to national defense, social policy and national economy with lower health-care and education spending. At the same time, the use of tax system as a resource for meeting the State's social obligations is increasingly constrained.